High-hardness silicone rubber and preparation method thereof

High-hardness silicone rubber prepared through specific formulas and two-stage vulcanization processes solves the problems of low hardness and serious wear of the foot pads of silicone rubber electronic products, and achieves higher hardness, wear resistance and durability.

CN119505548APending Publication Date: 2025-02-25HUBEI ZHENGAN NEW MATERIAL CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411840547.2
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-13
Publication Date
2025-02-25

AI Technical Summary

Technical Problem

The foot pads of existing silicone rubber electronic products are low in hardness and are prone to wear and cannot provide sufficient support, resulting in shaking or tilting of electronic products during use.

Method used

A specific formula of high-hardness silicone rubber, including methylvinyl silicone rubber, reinforced white carbon black, glass fiber powder, modifier and other raw materials are prepared through a two-stage vulcanization process to form silicone rubber with high hardness and appropriate elongation.

Benefits of technology

It improves the hardness and wear resistance of silicone rubber feet, enhances its stability and performance in long-term use and high temperature environments, reduces wear and improves the durability of the product.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005187871200000051
    Figure BDA0005187871200000051
  • Figure BDA0005187871200000061
    Figure BDA0005187871200000061
  • Figure BDA0005187871200000071
    Figure BDA0005187871200000071
Patent Text Reader

Abstract

The invention relates to the technical field of silicone rubber processing technologies, in particular to high-hardness silicone rubber and a preparation method thereof.The high-hardness silicone rubber is prepared from, by weight, 100 parts of methyl vinyl silicone rubber, 40-60 parts of reinforcing white carbon black, 10-15 parts of glass fiber powder, 7-12 parts of a structural control agent, 0.1-0.5 part of an inhibitor, 0.5-1 part of a platinum catalyst and 8-12 parts of a modifier. The modifier is obtained by mixing zinc stearate, zinc oxide whiskers and a lubricant, the silicone rubber prepared according to the formula has good hardness and elongation at break, it is ensured that the silicone rubber foot pad still has certain elongation while keeping high hardness, and the service life of the silicone rubber foot pad is prolonged. The silicone rubber foot pad can properly deform under the action of external force, so that impact and vibration are absorbed, and the durability of the product is improved. Meanwhile, the high-hardness silicone rubber foot pad can keep good performance and reduce abrasion when being used for a long time or rubbed. Meanwhile, the high-temperature resistance of the silicone rubber is improved, so that the silicone rubber can be used in a high-temperature environment.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application relates to the technical field of silicone rubber processing, and more specifically, to a high-hardness silicone rubber and a preparation method thereof. Background Art

[0002] Electronic product foot pads are small accessories that are usually installed on the bottom or side of electronic products to support the product, reduce vibration, prevent wear and provide a stable support surface. Existing electronic product foot pads are mainly made of foam plastic and silicone. Among them, foam plastic has good elasticity and cushioning properties, and has high air tightness and corrosion resistance. It is often used in electrical appliances, machinery, digital and other industries to play an anti-slip and cushioning role. Silicone rubber electronic product foot pads are soft and elastic. They can produce large deformations under very small external forces, and can return to their original state after the external force is removed, so that they can effectively absorb and cushion impact forces, protect electronic products from damage caused by falls or collisions, and are often used in computers, watches, mobile phones and other high-end electronic products.

[0003] However, after silicone rubber is prepared into electronic product pads, the hardness is relatively low. Silicone rubber pads with low hardness are more prone to wear when used for a long time or subjected to friction. When supporting electronic products, they cannot provide sufficient supporting force, causing the electronic products to shake or tilt during use, thereby affecting their stability and performance. Summary of the invention

[0004] In order to solve the problem of low hardness of silicone rubber electronic product pads, the present application provides a high-hardness silicone rubber and a preparation method thereof.

[0005] In the first aspect, the present application provides a high-hardness silicone rubber, which adopts the following technical solution: A high-hardness silicone rubber is prepared from the following raw materials in parts by weight: 100 parts of methyl vinyl silicone rubber Reinforced white carbon black 40-60 parts 10-15 parts of glass fiber powder 2-5 parts of hydrogen silicone oil 7-12 parts of structural control agent Inhibitor 0.1-0.5 parts Platinum catalyst 0.5-1 part Modifier 8-12 parts The modifier is obtained by mixing zinc stearate, zinc oxide whisker and lubricant.

[0006] By adopting the above technical solution, the prepared silicone rubber has good hardness and elongation at break, ensuring that the silicone rubber foot pad has a certain elongation while maintaining a high hardness, which helps the silicone rubber foot pad to deform appropriately when subjected to external forces, thereby absorbing shock and vibration and improving the durability of the product. At the same time, the high-hardness silicone rubber foot pad can maintain good performance and reduce wear when used for a long time or subjected to friction. At the same time, the high-temperature resistance of silicone rubber is improved so that it can be used in high-temperature environments.

[0007] In this application, reinforcing white carbon black and glass fiber powder are used as inorganic fillers, which have the characteristics of high strength and high modulus. They are closely combined with the silicone rubber matrix to form a tighter network structure, thereby improving the hardness and strength of silicone rubber. The hardness of silicone rubber is improved, which will cause the elongation at break of silicone rubber to decrease. In this application, by adding a modifier and using a structure control agent, silicone rubber can maintain a certain elongation at break while increasing the hardness, so that silicone rubber has a certain flexibility and elasticity, and can adapt to electronic products of different shapes and sizes. Zinc stearate and zinc oxide whiskers can enhance the hardness and wear resistance of silicone rubber, while lubricants help to improve processing performance and dispersibility. The synergistic effect of these ingredients makes high-hardness silicone rubber still have good elongation and processing performance while maintaining high hardness. Structural control agents play a key role in the vulcanization process of silicone rubber, which helps to adjust the crosslinking density and vulcanization speed. By accurately controlling the dosage and vulcanization conditions of the structural control agent, the balance between the hardness and elongation of silicone rubber is optimized.

[0008] In addition, the addition of glass fiber powder further enhances the hardness and modulus of silicone rubber, while improving its high temperature resistance. Glass fiber powder has high modulus and high strength, can withstand stress at high temperatures, and prevent silicone rubber from deforming or failing at high temperatures.

[0009] Preferably, the weight ratio of the zinc stearate, the zinc oxide whisker and the lubricant is 5:(3-6):1.

[0010] By adopting the above technical solution, the dosage of zinc stearate, zinc oxide whisker and lubricant is optimized, and the hardness, elongation at break and wear resistance of the silicone rubber foot pad are further improved, so that the silicone rubber foot pad can maintain stable performance during long-term use and is not prone to wear or deformation.

[0011] Preferably, the glass fiber powder is modified glass fiber powder, which is prepared by the following method: 1) mixing glass fiber powder, dimethylsilyl disiloxane and a solvent to obtain a premix; 2) Soaking diatomaceous earth in an acrylic resin solution, filtering, taking a filter residue, mixing the filter residue with a premix, ultrasonicating, filtering, taking a filter residue, and drying to obtain a modified glass fiber powder.

[0012] Adding glass fiber powder can improve the hardness and high temperature resistance of silicone rubber foot pads. However, due to the high hardness and rigidity of glass fiber powder, it is easy to break or unevenly distribute during processing.

[0013] By adopting the above technical solution, the dispersion uniformity of glass fiber powder in silicone rubber is improved, and the processing performance of glass fiber powder is improved. By mixing glass fiber powder with dimethylsilyl disiloxane and solvent to form a premix, and introducing diatomaceous earth treated with acrylic resin in the subsequent step, the compatibility and dispersibility of glass fiber powder with silicone rubber matrix can be effectively improved, which helps to reduce the breakage and uneven distribution of glass fiber powder during processing, and improve processing efficiency and product quality.

[0014] Wherein, in step 1), by mixing glass fiber powder with dimethylsilyl disiloxane and solvent, the dispersibility of glass fiber powder is improved, which is beneficial to subsequent operations. In step S2, by mixing diatomaceous earth and acrylic resin solution, a layer of acrylic resin is coated on the surface of diatomaceous earth, and then it is mixed with the premix, so that a layer of glass fiber powder is attached to the surface of diatomaceous earth, so that the glass fiber powder has better dispersibility, and the fracture and uneven distribution phenomenon during the processing are reduced. The addition of diatomaceous earth particles helps to improve the dispersibility of glass fiber powder in the mixture, reduce agglomeration and entanglement, and improve the uniformity and stability of modified glass fiber powder.

[0015] Preferably, the weight portions of the raw materials used to prepare the modified glass fiber powder are as follows: 10-15 parts of glass fiber powder 1-1.5 parts of dimethylsilyl disiloxane Solvent 15-20 parts 5-8 parts of diatomaceous earth 10-15 parts of acrylic resin solution The concentration percentage of the acrylic resin in the acrylic resin solution is 20-30%.

[0016] By adopting the above technical scheme, the amount of raw material for preparing modified glass fiber powder is optimized, the dispersibility of glass fiber powder in silicone rubber system is further improved, the possibility of glass fiber powder breakage is reduced, and the hardness, elongation and wear resistance of silicone rubber pad are improved.

[0017] Preferably, the average particle size of the diatomaceous earth is 50-100 microns.

[0018] By adopting the above technical solution, the average particle size of diatomaceous earth is optimized, so that the contact area between diatomaceous earth and glass fiber powder is increased, which helps to disperse it more evenly in the glass fiber powder during the mixing process. At the same time, the diatomaceous earth has good fluidity in the mixture, which helps to better fill and distribute it in the silicone rubber during the processing process, thereby obtaining a silicone rubber foot pad with better performance.

[0019] Preferably, the glass fiber powder needs to be sieved through a 2000-4000 mesh sieve.

[0020] By adopting the above technical solution, the fineness of the glass fiber powder is optimized, so that the glass fiber powder can be more effectively dispersed in the silicone rubber matrix to form more interface bonding points, thereby improving the hardness, elongation and wear resistance of the silicone rubber.

[0021] Preferably, the structure control agent is hexamethylcyclotrisilazane and / or hexamethyldisilazane.

[0022] By adopting the above technical solutions and optimizing the types of structure control agents, not only the hardness of the silicone rubber pads is improved, but also the viscosity of the silicone rubber can be reduced, making it easier to mix and process. They are also helpful in preparing electronic product pads with complex shapes.

[0023] Preferably, the methyl vinyl silicone rubber is obtained by mixing methyl vinyl silicone rubber with a molecular weight of 900,000-1.1 million and a vinyl molar content of 2-4% and methyl vinyl silicone rubber with a molecular weight of 400,000-800,000 and a vinyl molar content of 0.5-2% in a weight ratio of (4-9):1.

[0024] By adopting the above technical solution, the type and amount of methyl vinyl silicone rubber are optimized, and the hardness and elongation of silicone rubber foot pads are further balanced. High molecular weight silicone rubber provides better tensile strength and tear strength, while low molecular weight silicone rubber helps to improve the processing performance and fluidity of silicone rubber foot pads. The combination of the two is conducive to improving the tensile strength, wear resistance and hardness of silicone rubber.

[0025] Preferably, the reinforcing white carbon black is composed of white carbon black with an average particle size of 20-50 nm and white carbon black with an average particle size of 50-200 nm in a weight ratio of 3:(7-10).

[0026] By adopting the above technical solution, mixing white carbon black of different particle sizes can form a more uniform reinforcement network, thereby improving the hardness, wear resistance and elongation of silicone rubber. Mixing white carbon black of different particle sizes can form a more uniform reinforcement network, thereby improving the tensile strength, wear resistance and hardness of silicone rubber.

[0027] In a second aspect, the present application provides a method for preparing high-hardness silicone rubber, using the following technical solution: A method for preparing high-hardness silicone rubber comprises the following preparation steps: S1, mixing methyl vinyl silicone rubber, reinforcing white carbon black, glass fiber powder, structure control agent, hydrogen-containing silicone oil, inhibitor, platinum catalyst and modifier to obtain a mixture; S2. The mixture is vulcanized, the first stage vulcanization temperature is 160-180°C, and the vulcanization time is 5-10 minutes; the second stage vulcanization temperature is 190-200°C, and the vulcanization time is 1-2 minutes, to obtain high hardness silicone rubber.

[0028] By adopting the above technical solution, a mixture with high hardness and high strength is formed by mixing raw materials such as methyl vinyl silicone rubber, reinforcing white carbon black, and glass fiber powder. Then, through a two-stage vulcanization process, the hardness, tensile strength, elongation at break and wear resistance of silicone rubber are further improved. Among them, the first stage of vulcanization is carried out at a lower temperature for a longer time, which is conducive to the full cross-linking and curing of each component in the mixture; the second stage of vulcanization is carried out at a higher temperature for a short time, which further promotes the completion of the cross-linking reaction and further improves the hardness of the silicone rubber.

[0029] In summary, this application has the following beneficial effects: 1. By adding reinforcing white carbon black, glass fiber powder and specific modifiers, the hardness and elongation at break of high-hardness silicone rubber are improved, which can effectively resist wear caused by long-term use or friction. Among them, when glass fiber powder is added to silicone rubber, the glass fiber powder can bear part of the load, thereby improving the hardness and load-bearing capacity of silicone rubber. The modifier is composed of zinc stearate, zinc oxide whisker and lubricant. Zinc stearate and zinc oxide whisker can improve the hardness and wear resistance of silicone rubber; while the lubricant helps to improve the processing performance and dispersibility of silicone rubber. These ingredients work together to make silicone rubber have good elongation and processing performance while maintaining high hardness. DETAILED DESCRIPTION Example

[0030] Methyl vinyl silicone rubber was purchased from Dongguan Shuangao Plastic Co., Ltd. and is injection molding grade.

[0031] The hydrogen-containing silicone oil was purchased from Qingdao Baisenmao New Materials Co., Ltd., model BSM202.

[0032] Example 1 A high-hardness silicone rubber is prepared by the following method: S1, 1000 g of methyl vinyl silicone rubber, 400 g of reinforcing white carbon black (average particle size of 20-30 nm), 100 g of glass fiber powder (mesh size of 2000), 70 g of structure control agent (hexamethylcyclotrisilazane), 20 g of hydrogen-containing silicone oil, 1 g of inhibitor (1-ethynylcyclohexanol), 5 g of platinum catalyst and 80 g of modifier are mixed to obtain a mixture; S2. The mixture is vulcanized, the first stage vulcanization temperature is 160°C, and the vulcanization time is 5 minutes; the second stage vulcanization temperature is 190°C, and the vulcanization time is 1 minute, to obtain high hardness silicone rubber.

[0033] The platinum content in the platinum catalyst is 10000 ppm.

[0034] The modifier is composed of zinc stearate, zinc oxide whisker and lubricant (erucic acid amide) in a weight ratio of 5:3:1.

[0035] The difference between Example 2-3 and Example 1 is that the types of raw materials, amounts and experimental parameters for preparing high hardness silicone rubber are different. The specific differences are shown in Table 1: Table 1 Types, amounts and experimental parameters of raw materials for preparing high hardness silicone rubber in Examples 1-3 In Example 2, the modifier is composed of zinc stearate, zinc oxide whisker and lubricant (ethylene bisstearamide) in a weight ratio of 5:5:1, and the platinum content in the platinum catalyst is 5000 ppm.

[0036] In Example 3, the modifier is composed of zinc stearate, zinc oxide whisker and lubricant (stearic acid wax) in a weight ratio of 5:6:1, and the platinum content in the platinum catalyst is 1000 ppm.

[0037] Example 4 The acrylic resin solution is prepared by dissolving acrylic resin (purchased from Shandong Kunteng Chemical Co., Ltd., brand MB-2660) in ethyl acetate.

[0038] A high-hardness silicone rubber, the difference between this embodiment and embodiment 1 is that the glass fiber powder is modified glass fiber powder, which is prepared by the following method: 1) 100 g of glass fiber powder (average particle size of 1-2 μm), 10 g of dimethylsilyl disiloxane and 200 g of solvent (ethanol) were mixed to obtain a premix; 2) 50 g of diatomaceous earth (average particle size of 50-70 μm) is soaked in 100 g of acrylic resin solution, filtered, and the residue is taken. The residue is then mixed with the premix, ultrasonicated, filtered, and the residue is taken. The residue is dried to obtain modified glass fiber powder.

[0039] The concentration percentage of the acrylic resin in the acrylic resin solution is 20%.

[0040] The difference between Example 5-6 and Example 4 is that the types of raw materials, amounts and experimental parameters for preparing the modified glass fiber powder are different. The specific differences are shown in Table 2: Table 2 Types of raw materials, amounts and experimental parameters for preparing modified glass fiber powder in Examples 4-6 The concentration percentage of acrylic resin in the acrylic resin solution of Example 5 is 25%.

[0041] The concentration percentage of acrylic resin in the acrylic resin solution of Example 6 is 30%.

[0042] Example 7 A high-hardness silicone rubber. The difference between this embodiment and embodiment 4 is that dimethylsilyl disiloxane is not added in step 1).

[0043] Example 8 A high-hardness silicone rubber. The difference between this embodiment and embodiment 4 is that no acrylic resin is added.

[0044] Example 9 A high-hardness silicone rubber. The difference between this embodiment and embodiment 4 is that diatomaceous earth is not added.

[0045] Example 10 A high hardness silicone rubber. The difference between this embodiment and embodiment 1 is that the methyl vinyl silicone rubber is obtained by mixing methyl vinyl silicone rubber with a molecular weight of 900,000 and a vinyl molar percentage of 2% and methyl vinyl silicone rubber with a molecular weight of 400,000 and a vinyl molar percentage of 0.5% in a weight ratio of 4:1.

[0046] Embodiment 11 A high hardness silicone rubber. The difference between this embodiment and embodiment 4 is that the methyl vinyl silicone rubber is obtained by mixing methyl vinyl silicone rubber with a molecular weight of 1.1 million and a vinyl molar percentage of 4% and methyl vinyl silicone rubber with a molecular weight of 800,000 and a vinyl molar percentage of 2% in a weight ratio of 9:1.

[0047] Example 12 A high-hardness silicone rubber. The difference between this embodiment and embodiment 1 is that the reinforcing white carbon black is composed of white carbon black with an average particle size of 20-30nm and white carbon black with an average particle size of 50-100nm in a weight ratio of 3:7.

[0048] Embodiment 13 A high-hardness silicone rubber. The difference between this embodiment and embodiment 1 is that the reinforcing white carbon black is composed of white carbon black with an average particle size of 31-50nm and white carbon black with an average particle size of 150-200nm in a weight ratio of 3:10.

[0049] Embodiment 14 A high-hardness silicone rubber. The difference between this embodiment and embodiment 10 is that the reinforcing white carbon black is composed of white carbon black with an average particle size of 31-50nm and white carbon black with an average particle size of 150-200nm in a weight ratio of 3:10.

[0050] Comparative Example Comparative Example 1 A high-hardness silicone rubber. The difference between this embodiment and embodiment 1 is that silicon nitride is used instead of glass fiber powder.

[0051] Comparative Example 2 A high-hardness silicone rubber. The difference between this embodiment and embodiment 1 is that silicon micropowder is used instead of a modifier.

[0052] Comparative Example 3 A high-hardness silicone rubber. The difference between this embodiment and embodiment 1 is that the modifier is composed of zinc stearate and zinc oxide whisker in a weight ratio of 5:3.

[0053] Comparative Example 4 A high-hardness silicone rubber. The difference between this embodiment and embodiment 1 is that the modifier is composed of zinc stearate and a lubricant in a weight ratio of 5:1.

[0054] Comparative Example 5 A high-hardness silicone rubber. The difference between this embodiment and embodiment 1 is that the modifier is composed of zinc oxide whiskers and lubricant in a weight ratio of 3:1.

[0055] Detection method / test method Hardness: Tested in accordance with B / T531.1-2008.

[0056] Elongation at break and tensile strength: tested in accordance with GB / T528-2009.

[0057] Wear resistance: The wear resistance of the samples was tested according to GB / T 9867-2008 Determination of wear resistance of vulcanized rubber or thermoplastic rubber (rotating roller abrasion machine method), using the No. 2 standard reference rubber in the standard, and the average relative wear index / % as the evaluation index. The wear index refers to the ratio of the volume wear of the reference rubber to the volume wear of the test rubber. The experimental data is shown in Table 3: Table 3 Experimental data of Examples 1-13 and Comparative Examples 1-3 By comparing Example 1 with Comparative Example 1, the hardness, tensile strength and wear resistance values ​​of Comparative Example 1 are all higher than those of Example 1, but the elongation at break of Comparative Example 1 is lower than that of Example 1, indicating that the elongation at break of silicone rubber can be greatly improved by using glass fiber powder together with methyl vinyl silicone rubber, reinforcing silica and other raw materials.

[0058] By comparing Example 1 with Comparative Examples 2-5, the values ​​of hardness, tensile strength, elongation at break and wear resistance in Comparative Example 1 are all lower than those in Example 1, indicating that the hardness, tensile strength, elongation at break and wear resistance of silicone rubber can be improved by preparing a modifier using zinc stearate, zinc oxide whisker and a lubricant and then using it together with raw materials such as methyl vinyl silicone rubber, reinforcing silica, and glass fiber powder.

[0059] By comparing Example 1 with Examples 4-6, the values ​​of hardness, tensile strength, elongation at break and wear resistance in Examples 4-6 are all higher than those in Example 1; By comparing Example 4 with Examples 7-9, the values ​​of hardness, tensile strength, elongation at break and wear resistance in Examples 7-9 are all lower than those in Example 4; It can be seen from the experimental data of Examples 1, 4-6 and Examples 4, 7-9 that the modified glass fiber powder prepared by the formula and preparation process in this application is beneficial to improving the hardness, tensile strength, elongation at break and wear resistance of silicone rubber.

[0060] By comparing Example 1 with Example 10, the values ​​of hardness, tensile strength, elongation at break and wear resistance in Example 10 are all higher than those in Example 1; By comparing Example 4 with Example 11, the values ​​of hardness, tensile strength, elongation at break and wear resistance in Example 11 are all higher than those in Example 4; It can be seen from the experimental data of Examples 1, 10 and Examples 4, 11 that optimizing the type and amount of methyl vinyl silicone rubber is beneficial to improving the hardness, tensile strength, elongation at break and wear resistance of silicone rubber.

[0061] By comparing Example 1 with Example 12, the values ​​of hardness, tensile strength, elongation at break and wear resistance in Example 12 are all higher than those in Example 1; By comparing Example 4 with Example 13, the values ​​of hardness, tensile strength, elongation at break and wear resistance in Example 13 are all higher than those in Example 4; By comparing Example 10 with Example 14, the values ​​of hardness, tensile strength, elongation at break and wear resistance in Example 14 are all higher than those in Example 10; It can be seen from the experimental data of Examples 1, 10 and Examples 4, 11 and 10 and 14 that the hardness, tensile strength, elongation at break and wear resistance of silicone rubber can be improved by combining reinforcing silica with different average particle sizes.

[0062] This specific embodiment is merely an explanation of the present application and is not a limitation of the present application. After reading this specification, those skilled in the art may make modifications to the present embodiment without any creative contribution as needed, but such modifications are protected by the patent law as long as they are within the scope of the claims of the present application.

Claims

1. A high hardness silicone rubber, characterized in that: Prepared from the following raw materials in parts by weight: 100 parts of methyl vinyl silicone rubber Reinforced white carbon black 40-60 parts 10-15 parts of glass fiber powder 7-12 parts of structural control agent 2-5 parts of hydrogen silicone oil Inhibitor 0.1 -0.5 parts Platinum catalyst 0.5-1 part Modifier 8-12 parts The modifier is obtained by mixing zinc stearate, zinc oxide whisker and lubricant.

2. The high hardness silicone rubber according to claim 1, characterized in that: The weight ratio of the zinc stearate, the zinc oxide whisker and the lubricant is 5:(3-6):

1.

3. The high hardness silicone rubber according to claim 2, characterized in that: The glass fiber powder is a modified glass fiber powder, which is prepared by the following method: 1) mixing glass fiber powder, dimethylsilyl disiloxane and solvent to obtain a premix; 2) Soak the diatomaceous earth in an acrylic resin solution, filter, take the filter residue, mix the filter residue with the premix, perform ultrasonic treatment, filter, take the filter residue, and dry to obtain the modified glass fiber powder.

4. The high hardness silicone rubber according to claim 1, characterized in that: The weight portions of the raw materials used to prepare the modified glass fiber powder are as follows: 10-15 parts of glass fiber powder 1-1.5 parts of dimethylsilyl disiloxane Solvent 15-20 parts 5-8 parts of diatomaceous earth 10-15 parts of acrylic resin solution The concentration percentage of the acrylic resin in the acrylic resin solution is 20-30%.

5. The high-hardness silicone rubber according to claim 4, characterized in that: The average particle size of the diatomaceous earth is 50-100 microns.

6. The high-hardness silicone rubber according to claim 4, characterized in that: The glass fiber powder needs to pass through a 2000-4000 mesh sieve.

7. The high-hardness silicone rubber according to claim 1, characterized in that: The structure control agent is hexamethylcyclotrisilazane and / or hexamethyldisilazane.

8. The high-hardness silicone rubber according to claim 1, characterized in that: The methyl vinyl silicone rubber is obtained by mixing methyl vinyl silicone rubber with a molecular weight of 900,000-1.1 million and a vinyl molar content of 2-4% and methyl vinyl silicone rubber with a molecular weight of 400,000-800,000 and a vinyl molar content of 0.5-2% in a weight ratio of (4-9):

1.

9. The high-hardness silicone rubber according to claim 1, characterized in that: The average particle size of the reinforcing white carbon black is 3:(7-10) by weight of white carbon black with an average particle size of 20-50 nm and white carbon black with an average particle size of 50-200 nm.

10. A method for preparing the high-hardness silicone rubber according to any one of claims 1 to 9, characterized in that: The method comprises the following preparation steps: S1, mixing methyl vinyl silicone rubber, reinforcing white carbon black, glass fiber powder, structure control agent, hydrogen-containing silicone oil, inhibitor, platinum catalyst and modifier to obtain a mixture; S2. The mixture is vulcanized, the first stage vulcanization temperature is 160-180°C, and the vulcanization time is 5-10 minutes; the second stage vulcanization temperature is 190-200°C, and the vulcanization time is 1-2 minutes, to obtain high hardness silicone rubber.